A TEACHER'S MORAL AND ETHICAL STANDARDS ARE THE KEY TO HIS SUCCESS - Sayyora Ganieva (Web of Journals Publishing, 2025)
Activity known one field with practitioner to people relevant moral There are also norms and requirements. Such morality professional ethics It is called. Everyone in society dominant was morality with profession morality between known one attitude This is common. with privacy between is a relationship. Profession morality universal morality theory rules and disadvantages in itself embodies, clarifies and develops.
Keywords: Pedagogical communication, culture, profession morality, speech culture, suggestive ability.